2021
DOI: 10.5271/sjweh.3993
|View full text |Cite|
|
Sign up to set email alerts
|

Physical activity at work may not be health enhancing. A systematic review with meta-analysis on the association between occupational physical activity and cardiovascular disease mortality covering 23 studies with 655 892 participants

Abstract: While the beneficial association between leisure-time physical activity and cardiovascular disease (CVD) mortality has been widely documented, occupational physical activity was not found to have a beneficial association with CVD mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 80 publications
4
56
1
Order By: Relevance
“…The results from our study suggest that the ‘physical activity paradox’ applies even to associations between cardiovascular work intensity and musculoskeletal pain, complementing previous studies of cardiovascular health [ 2 , 3 , 4 ], cancer [ 5 ], and all-cause mortality [ 6 ]. Even though participants spent similar amounts of time in physical activity at work and during leisure (cf.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results from our study suggest that the ‘physical activity paradox’ applies even to associations between cardiovascular work intensity and musculoskeletal pain, complementing previous studies of cardiovascular health [ 2 , 3 , 4 ], cancer [ 5 ], and all-cause mortality [ 6 ]. Even though participants spent similar amounts of time in physical activity at work and during leisure (cf.…”
Section: Discussionsupporting
confidence: 85%
“…While it has consistently been shown that regularly engaging in high-intensity leisure-time physical activity (LTPA) is associated with positive health effects, occupational physical activity (OPA) with high intensity is associated with no beneficial, or even negative, health effects. This phenomenon, which is referred to as the ‘physical activity paradox’ [ 1 ], has been shown for various health outcomes such as cardiovascular health [ 2 , 3 , 4 ], some cancers [ 3 , 5 ], sleep quality [ 3 ], and all-cause mortality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…PhenoAgeAA was associated with job strain, active work-compared to reference low strain-in both AGING OPA may not be associated with good health, in contrast with leisure-time physical activity [37].…”
Section: Phenoage and Grimaage Aamentioning
confidence: 81%
“…The favourable effects of leisure time physical activity on the risk of cardiovascular disease (CVD) and mortality are well established [ 1 7 ]. In contrast, occupational physical activity may increase the risk of both CVD-specific and all-cause mortality, at least among men [ 8 10 ], and evidence on the association between occupational physical activity and risk factors for CVD, risk of ischemic heart disease (IHD), and major cardiovascular events is inconclusive [ 9 14 ]. The contrasting health effects from physical activity during leisure and work have been referred to as the physical activity health paradox [ 15 ].…”
Section: Introductionmentioning
confidence: 99%